BEYOND MOSQUITO BITES: ANALYZING MALARIA RISK FACTORS IN SOUTHERN NIGERIA - Said Baadel; Christie Akwaowo; Jeremiah C. Obi; Shalom Benson; Malaadh Baadel; Daniel Asuquo; Nnette Ekpenyong; Kingsley Attai; Humphrey Sabi; Faith-Michael Uzoka (Problems of Infectious and Parasitic Diseases)
This study investigates how various risk factors affect the prevalence of febrile diseases, with a focus on malaria in the southern states of Nigeria. The study employed Pearson correlation and multilinear regression analyses to examine the relationships between risk factors and disease prevalence. Pearson correlation analysis revealed that genetic conditions, high blood pressure, and direct contact with infected individuals were negatively correlated with malaria, while poor personal hygiene, substandard living conditions, and exposure to endemic areas had weak positive correlations. The strongest association was found with mosquito bites, which also had the highest unstandardized beta coefficient among the factors studied. Nevertheless, the study also highlights secondary risk factors, such as poor living conditions and hygiene, which are often overlooked in malaria intervention programs. These factors, although not as strong as mosquito exposure, can exacerbate the risk of infection, particularly in vulnerable populations living in impoverished areas. These results highlight the critical role of mosquito exposure in malaria and emphasize the need for targeted interventions in such areas. The findings can be beneficial to clinicians, general public, and all stakeholders involved in the fight against malaria.